2022
DOI: 10.2478/aoas-2021-0075
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal programming of the small intestine in piglets: the effect of supplementation with 3-hydroxy-3-methylbutyric acid (HMB) in pregnant sows on the structure of jejunum of their offspring

Abstract: When discussing the scale of the occurrence of diseases of the digestive system in farm animals, particularly pigs in the weaning period, it may be beneficial to study physiological and nutritional factors that could potentially affect the growth, development, and modelling of the structure and function of the digestive tract. Taking into account the reports on the beneficial effects of ß-hydroxy-ß-methylbutyrate (HMB) administration in the prenatal period on the development of various systems it was assumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The analyses were performed using ImageJ software 82 . PSR staining was used distinguish between type I and type III collagen in examined SI samples, where type I (mature) collagen fibres appear orange or red, and type III (immature) fibres appear green in polarized light 83 , 84 .…”
Section: Methodsmentioning
confidence: 99%
“…The analyses were performed using ImageJ software 82 . PSR staining was used distinguish between type I and type III collagen in examined SI samples, where type I (mature) collagen fibres appear orange or red, and type III (immature) fibres appear green in polarized light 83 , 84 .…”
Section: Methodsmentioning
confidence: 99%
“…Upon arrival, hens were kept in cages accommodating two birds per cage, in compliance with the established housing regulations for research involving farm animals in the field of agriculture (cage dimensions of 30 × 120 × 50 cm, w × d × h, ensuring 1800 cm 2 of floor space per hen). The experimental timeline consisted of a pre-experimental phase (age weeks [18][19][20][21][22][23][24][25][26][27][28][29][30], during which all birds were provided with the standard soybean-wheat-cornbased commercial pre-laying and laying diet. At the commencement of the experimental phase (age weeks 31-60), the birds were randomly allocated to either the control group or the group receiving dietary supplementation with ß-Hydroxy-ß-methylbutyrate (the HMB group).…”
Section: Birds and Experimental Dietsmentioning
confidence: 99%
“…Studies on pigs supplemented with HMB have shown that it regulates lipid metabolism, promoting fat oxidation, which could potentially improve body composition and aid in fat loss [22][23][24]. Additionally, HMB enhanced piglets bone health by promoting bone formation, reducing resorption, and increasing bone density [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The reaction areas were manually delineated using the freehand selection tool. The staining intensity was determined based on the 'average grayscale value' parameter [27]. The grayscale pixel color value ranged from 0 to 255, where 0 was the darkest shade (black pixel) and 255 was the lightest shade (white pixel).…”
Section: Evaluation Of the Ihc Reaction Intensitymentioning
confidence: 99%